Antagonistic Activity of Lactic Acid Bacteria Against Pathogenic Vibrios and Their Potential Use as Probiotics in Shrimp (Penaeus vannamei) Culture - Thompson, John; Weaver, Mark A.; Lupatsch, Ingrid; Shields, Robin J.; Plummer, Sue; Coates, Christopher J.; Rowley, Andrew F. (Frontiers in Marine Science, 2022)
Probiotic use in aquaculture settings can be an approach for disease control and dietary supplementation. We assessed the antagonistic effect of culture supernatants of lactic acid bacteria on the growth of known shrimp pathogens, Vibrio (Listonella) anguillarum, Vibrio alginolyticus, and V. harveyi, using a quantitative microplate bioassay. Supernatants from Lactobacillus curvatus subsp. curvatus, L. plantarum, and Pediococcus acidolactici significantly inhibited the growth of these vibrios. The active component(s) were heat stable (> 100°C) and resistant to freeze-thawing. Most of this inhibitory activity was brought about by the production of an acid pH; however, there was evidence for other factors playing a role. In the search for novel probiotic bacteria, an organism was isolated from the gastrointestinal tract of healthy whiteleg shrimp (Penaeus vannamei)—identified tentatively as Carnobacterium maltaromaticum. This isolate, however, had less potent vibriocidal activity than the lactic acid bacteria and reduced shrimp survival at a dose of 1 × 107 bacteria/shrimp. During a 28-day feeding trial, juvenile P. vannamei fed with L. plantarum supplemented diets showed no gross changes in growth parameters compared with the control. We suggest that lactic acid bacteria could be incorporated into biofloc formulations to purge the growth of pathogenic vibrios in pond settings, rather than being fed directly to shrimp.